1999
DOI: 10.1080/00028899908984467
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Respirator Inspiratory Resistance Level on Constant Load Treadmill Work Performance

Abstract: Respirator inspiratory resistance can affect performance times, especially when the experiment is optimized to elicit respiratory stress. Twelve subjects performed on a treadmill at constant speeds and grades chosen to result in performance times of 5-15 min. Six levels of inspiratory resistance were used, ranging from 0.78 to 7.64 cm H2O.sec/L. The results showed that performance times decrease linearly with resistance level, and no threshold resistance value is apparent. Inspiratory resistance also induces h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 0 publications
6
43
0
Order By: Relevance
“…14 Respiratory inspiratory resistance induces hypoventilation with lower minute volumes and lower O 2 consumption values at higher resistances. 15,16 Average O 2 consumption rates and minute ventilation also decrease linearly with increased expiratory resistances, indicating that increases in expiratory resistance result in a considerable level of hypoventilation. 17 Hypoventilation while wearing respirators causes higher amounts of blood lactate.…”
Section: Introductionmentioning
confidence: 92%
“…14 Respiratory inspiratory resistance induces hypoventilation with lower minute volumes and lower O 2 consumption values at higher resistances. 15,16 Average O 2 consumption rates and minute ventilation also decrease linearly with increased expiratory resistances, indicating that increases in expiratory resistance result in a considerable level of hypoventilation. 17 Hypoventilation while wearing respirators causes higher amounts of blood lactate.…”
Section: Introductionmentioning
confidence: 92%
“…Excessive inhalation resistance causes an increase in heart rate and oxygen consumption, resulting in physiological discomfort, which further influences work performance. Therefore, numerous studies have emphasized human factors and ergonomics by investigating the physiological characteristics of users; [21][22][23][24][25][26][27][28][29] however, few studies have investigated the aerodynamic behaviors of gas mask canisters.…”
mentioning
confidence: 99%
“…Similar decrements in JVE at steady-state work rates requiring 80% to 85% of P02 max have also been reported using much smaller inspiratory resistive loads (below 8 cmH 2 0-L-1 S). (19, 47,73,87) Applied ERL under steady-state exercise conditions tend to also reduce VE but again, the magnitude of these reductions is much less than those found for IRL. (21,60,118,136) The changes in JVE during non-steady-state maximal efforts mimic those reported during steady-state work for individually applied inspiratory (36,103,107) and expiratory resistances.…”
Section: 1mentioning
confidence: 76%
“…Others found reductions in P"E values on the order of about 15% to 43% under high-intensity constant load work conditions with similar respirator conditions. (59,73) Due to these large decrements in P)E but relatively unchanged or slightly reduced rates of oxygen consumption, both Hermansen et al (59) and Jette et al (70) found that APR wear reduced JIEI'02 compared to the unmasked conditions at high work rates. Jette et al (70) reported a 9% reduction in PE/IJ'02 with an APR compared to the unmasked condition at maximal work.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation